One step from the deep ocean: Linking research and governance for the Tagus river estuary and the Lisbon canyon system – A conference report. (October 2022) - Stratoudakis, Yorgos; Caetano, Miguel; Afonso, Cláudia; Bartilloti, Cátia; dos Santos, Antonina; Terrinha, Pedro; Figueiredo, Ivone; Miranda, Miguel; Costa, José Lino; Caçador, Isabel; Fonseca, Vanessa; Chainho, Paula; et al.
Abstract: This report summarizes current threats to the Tagus estuary and adjacent ecosystems, presented in Lisbon in June 2021, and prioritizes actions to maintain or improve ecosystem services for a densely populated area close to the deep ocean.